## Solving the Equation: (5y + 4) + (-2y + 6) = ?

This equation involves combining like terms to simplify and solve for the variable 'y'. Here's how we can do it:

### Understanding the Equation

The equation (5y + 4) + (-2y + 6) = ? is asking us to simplify the expression on the left side of the equation.

### Combining Like Terms

**Identify like terms:**'5y' and '-2y' are like terms because they both have 'y'. Similarly, '4' and '6' are like terms because they are constants.**Combine the 'y' terms:**5y + (-2y) = 3y**Combine the constant terms:**4 + 6 = 10

### Simplified Equation

After combining like terms, the simplified equation becomes:

**3y + 10 = ?**

### Solving for 'y'

To solve for 'y', we need more information. The equation is incomplete. We need a value on the right side of the equation to determine the value of 'y'.

**For example:**

If the equation was (5y + 4) + (-2y + 6) = **16**, we could solve for 'y' as follows:

**Simplify the left side:**3y + 10 = 16**Subtract 10 from both sides:**3y = 6**Divide both sides by 3:**y = 2

Therefore, if the equation was (5y + 4) + (-2y + 6) = 16, then **y = 2**.